Consumption of Brazil nuts with high selenium levels increased inflammation biomarkers in obese women: A randomized controlled trial - Duarte, Graziela Biude Silva (2019)
Objective: Increased inflammatory response is an important factor in the pathophysiology of obesity. The mineral selenium (Se), of which one of the main food sources is the Brazil nut, has important antioxidant and anti-inflammatory functions through the action of selenoproteins. Thus, the evaluation of the influence of this micronutrient in this context is of great relevance. The aim of this study was to evaluate the effects of Brazil nut intake with high Se concentrations on inflammatory biomarkers and its relation to Se status in obese women. Methods: A randomized controlled clinical trial was carried out with 55 women recruited at Clinical Hospital in Sao Paulo, Brazil. Patients were randomly assigned to either the Brazil nut group (BN) or the control group ~ (CO) and followed up for 2 mo. The BN group consumed 1 unit/d of Brazil nuts (» 1261 mg/Se); the CO group did not receive any intervention. At baseline and after 2 mo, analysis of biochemical parameters related to Se status, oxidative stress, and inflammatory biomarkers were performed. Results: At baseline, both groups did not present Se deficiency. In the BN group, a significant increase (P < 0.05) in all Se biomarkers and in gene expression of several proinflammatory parameters (interleukin-6, tumor necrosis factor-a, and Toll-like receptors 2 and 4) were observed after the intervention period. No changes were observed for the CO group. Conclusion: Although there were no changes in plasma inflammatory biomarkers levels, a significant increase in gene expression may be an indication of a proinflammatory stimulus in obesity, induced by the consump- tion of Brazil nuts with high Se levels.